CURRICULUM DESIGN FOR TRAINING SPECIALISTS IN THE SPHERE OF UPBRINGING IN THE CONTEXT OF PROFESSIONAL STANDARDS - Irina N Emelyanova (Peoples' Friendship University of Russia (RUDN University), 2017)
The article examines the new guidelines and priorities for modelling specialists' training in the field of upbringing in the context of the new professional standard.Research method - content analysis for the professional standard "Specialist in the field of upbringing". The content analysis was carried out according to the types of activities that are identified in the federal state educational standards of the pedagogical direction: pedagogical, project, cultural and educational, research, methodical, and managerial activity. The study revealed a priority of pedagogical, methodological, and managerial contents for training specialists in the field of upbringing. Socio-cultural content lags behind, scientific research content is reduced to zero.Polemical issues: "What does the emergence of new spheres of activities 'expert in the field of social upbringing' give us? To what degree professional and educational standards should be identical?" are considered. The need for professional training model to focus not only on the priority content outlined in the professional standards is proved. It is necessary to set cultural and developmental tasks.The model for socio-pedagogical training of a specialist in the field of social upbringing is offered on the example of the master's level "Methodology and methods of social upbringing" educational program implemented at the Tyumen State University. A general conclusion is drawn on the need to establish a new educational policy in the field of social pedagogical training.